FAKTOR TERJADINYA TINDAK KECURANGAN PENGELOLAAN DANA DESA DENGAN PENGGUNAAN SISKEUDES SEBAGAI VARIABEL MEDIASI (STUDI PADA PERANGKAT DESA SE KABUPATEN TEGAL) - Arifany Ferida; Mohammad Alfian; Nizar Fahrezi Majid (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
Village development is one of the focuses of President Joko Widodo's administration in the second term. Villages can maximize the use of Village Funds in the process of village development. Many benefits are felt by the village from the existence of village fund. However, with the great benefits and freedom in managing the village funds, there was a misuse of village funds. This study conducted a study on the influence of Money Ethics and Religiosity on Village Fund Management Fraud by including the use of SISKEUDes as a mediation variable. Respondents from this study totaled 168 with a sample selection method using random sampling. The statistical analysis method in this study used the Partial Least Square (PLS) method and used the SmartPLS 3 statistical test tool. Based on the statistical tests conducted, it is found that Money Ethics has an effect on Fraud Acts of Village Fund Management, while Religiosity has no effect. The use of SISKEUDes does not fully mediate the effect of Money Ethics on Fraud Acts of Village Fund Management but does not succeed in mediating the influence of Religiosity on Fraud Acts of Village Fund Management.